Exploring the effect of the menstrual cycle or oral contraception on elite athletes` training responses when workload is not objectively quantifiable: the MILS approach and findings from female Olympians - De Larochelambert, Q.; Hamri, I.; Chassard, T.; Storme, F.; Dupuit, M.; Diry, A.; Toussaint, J.-F.; Louis, P. Y.; Coulmy, N.; Antero, J. D. S. (BMJ Open Sport & Exercise Medicine, 2024)
Objectives Develop the Markov Index Load State (MILS) model, based on hidden Markov chains, to assess athletes` workload responses and investigate the effects of menstrual cycle (MC)/oral contraception (OC), sex steroids hormones and wellness on elite athletes` training.